Germination and emergence of passion fruit (Passiflora edulis) seeds obtained by self- and open-pollination - Santos, Carlos Eduardo Magalhães dos; Morgado, Marcos Antônio Dell’Orto; Matias, Rosana Gonçalves Pires; Wagner Júnior, Américo; Bruckner, Claudio Horst (Acta Scientiarum. Agronomy, 2015)
Seed dormancy is an important adaptive mechanism in many species and is generally lost during plant domestication because of selection that occurs through the collection and planting of seeds. We compared germination and seedling emergence in selfed and open-pollinated progenies obtained from eight passion fruit vines (genotypes). Self-pollination was performed at the button stage to overcome self-incompatibility. The experiment was a randomized block design in a factorial scheme (2 x 8; type of progeny x genotypes) with four replicates and 50 seeds per experimental unit. At 14, 21 and 28 days after sowing, the germination percentage and the emergence speed index were analyzed. The total length of seedlings (cm), shoot length (cm), radicle length (cm) and total dry matter of seedlings (g) were evaluated 28 days after sowing. The mass of 100 seeds (g) was determined before sowing. Differences were noted between genotypes and progeny types with respect to germination and emergence speed. In general, seeds obtained by selfing exhibited earlier germination and a higher emergence speed. It was concluded that seed dormancy is associated with the genotype of the embryo and is most likely conditioned by a dominant genetic effect.